Effects of ValoproWin and Formulation Strategy on Nursery Pig Performance and Fecal Dry Matter - Julian Arroyave; Mike D. Tokach; Jason C. Woodworth; Joel M. DeRouchey; Robert D. Goodband; Katelyn N. Gaffield; Jordan T. Gebhardt; Pau Salgado-López; David Guillou; Noëmie Lemoine (Kansas Agricultural Experiment Station Research Reports, 2025)
A total of 335 pigs (initially 12.3 ± 1.91 lb) were used to evaluate the effect of ValoproWin (VLPW) level and formulation strategy on nursery growth performance and fecal dry matter (DM). ValoproWin is a fiber ingredient that contains a purified source of coarse indigestible fiber, oat hulls, and yeast autolysate. At weaning, pigs were randomly assigned within two body weight (BW) blocks to one of the five dietary treatments in a generalized randomized block design. There were four or five pigs per pen and 14 replicate pens per treatment. Experimental diets were fed for 23 d, and then pigs were fed a common diet for 22 d. Dietary treatments were arranged in a 2 × 2 + 1 factorial design, with the main effects of added VLPW (2.5 or 5%) and formulation strategy (diluted or adjusted). An additional control treatment, which contained no VLPW, was included for comparison. In the diluted diets, VLPW was added at the expense of the complete diet without further adjustments to the formulation, resulting in nutrient dilution proportional to the VLPW inclusion. In contrast, adjusted diets were reformulated to maintain a similar nutrient composition to the control diet, regardless of VLPW addition. No significant interactions between VLPW inclusion or formulation strategy were observed for any of the performance criteria or periods. For the experimental period (d 0 to 23), pigs fed the diluted diets tended (P = 0.091) to have greater ADFI than those fed the adjusted diets. No differences were observed in ADG between formulation strategies. Consequently, pigs fed the adjusted diets tended (P = 0.084) to have improved F/G compared with those fed diluted diets. No significant main effects of VLPW level were observed for ADG and ADFI; however, pigs fed diets containing 5% of VLPW tended (P = 0.056) to have worse F/G compared with those fed diets containing 2.5% of VLPW. Also, increasing VLPW from 0 to 5% tended (P = 0.051) to linearly worsen F/G in the diluted diets but not in the adjusted diets. For the overall period (d 0 to 45), no main effects of the formulation strategy were observed for any of the performance parameters. However, pigs fed diets with 5% of VLPW during the experimental period tended (P = 0.059) to have poorer F/G compared with those fed diets with 2.5% VLPW. No significant effect of formulation strategy was observed for fecal DM. However, fecal DM linearly increased (P < 0.001) on d 10 as VLPW inclusion increased, independent of formulation strategy. At d 24, fecal DM tended to linearly increase (P = 0.098) as VLPW inclusion increased in the adjusted formulation strategy. In conclusion, the effect of added VLPW was independent of the formulation strategy. Increasing dietary VLPW improved fecal DM, particularly on d 10; however, F/G tended to worsen as VLPW level increased during both experimental and overall periods. During the experimental period, pigs fed the diluted diets had greater ADFI and poorer F/G than those fed the adjusted diets, although these differences were not maintained overall.
Keywords: Fecal dry matter; fiber; growth performance; nursery pig